2012
DOI: 10.1186/1475-2875-11-121
|View full text |Cite
|
Sign up to set email alerts
|

Access, acceptability and utilization of community health workers using diagnostics for case management of fever in Ugandan children: a cross-sectional study

Abstract: BackgroundUse of diagnostics in integrated community case management (iCCM) of fever is recognized as an important step in improving rational use of drugs and quality of care for febrile under-five children. This study assessed household access, acceptability and utilization of community health workers (CHWs) trained and provided with malaria rapid diagnostic tests (RDTs) and respiratory rate timers (RRTs) to practice iCCM.MethodsA total of 423 households with under-five children were enrolled into the study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 40 publications
8
72
3
1
Order By: Relevance
“…The highly positive perceptions of RDTs demonstrated by patients in this study correspond closely with other similar studies conducted in Ghana, Tanzania and Uganda [20,21,23-25]. Others have also identified that RDT acceptability is based on its perceived role in aiding the clinician to reach a more definitive diagnosis and prescribe the right treatment for their illness [20,23].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The highly positive perceptions of RDTs demonstrated by patients in this study correspond closely with other similar studies conducted in Ghana, Tanzania and Uganda [20,21,23-25]. Others have also identified that RDT acceptability is based on its perceived role in aiding the clinician to reach a more definitive diagnosis and prescribe the right treatment for their illness [20,23].…”
Section: Discussionsupporting
confidence: 85%
“…In general, these studies have explored the ‘acceptability’ of the use of RDTs to communities, including patients and caregivers of children [20-25], often reporting high levels of acceptability and positive perceptions of RDTs. However, it is important to understand not only whether tests are acceptable or not to those receiving them, but also how the tests are experienced by patients in practice; studying the technology in action , from the patient’s perspective [26].…”
Section: Introductionmentioning
confidence: 99%
“…Will iCCM encourage drug 'overtreatment', resulting in drug resistance? Addition of rapid diagnostic testing to iCCM (proven feasible elsewhere in Uganda and sub-Saharan Africa) 20,29,39 should be seriously considered.…”
Section: Discussionmentioning
confidence: 99%
“…Such targeting would also help reduce significant inequities found in malaria diagnosis, which must be addressed going forward. Integrated community case management with RDT-based malaria diagnosis has been successfully piloted in a number of settings by both community health workers and drug shop owners (39, 40), and it is a promising approach for bringing quality care to remote areas underserved by the formal health system.…”
Section: Discussionmentioning
confidence: 99%